Genome-wide systematic characterization of the bZIP transcriptional factor family in tomato (Solanum lycopersicum L.). (December 2015) - Li, Dayong; Fu, Fuyou; Zhang, Huijuan; Song, Fengming
Abstract Background Transcription factors of the basic leucine zipper (bZIP) family represent exclusively in eukaryotes and have been shown to regulate diverse biological processes in plant growth and development as well as in abiotic and biotic stress responses. However, little is known about the bZIP family in tomato (Solanum lycopersicum L.). Methods TheSlbZIP genes were identified using local BLAST and hidden Markov model profile searches. The phylogenetic trees, conserved motifs and gene structures were generated by MEGA6.06, MEME tool and gene Structure Display Server, respectively. The syntenic block diagrams were generated by the Circos software. The transcriptional gene expression profiles were obtained using Genevestigator tool and quantitative RT-PCR. Results In the present study, we carried out a genome-wide identification and systematic analyses of 69SlbZIP genes that distributes unevenly on the tomato chromosomes. This family can be divided into 9 groups according to the phylogenetic relationship among the SlbZIP proteins. Six kinds of intron patterns (a –f ) within the basic and hinge regions are defined. The additional conserved motifs and their presence of the group specificity were also identified. Further, we predicted the DNA-binding patterns and the dimerization property on the basis of the characteristic features in the basic and hinge regions and the leucine zipper, respectively, which supports our classification greatly and helps to classify 24 distinct subfamilies. Within the SlbZIP family, a total of 40SlbZIP genes are located in the segmental duplicate regions in the tomato genome, suggesting that the segment chromosomal duplications contribute greatly to the expansion of the tomato SlbZIP family. Expression profiling analyses of 59SlbZIP genes using quantitative RT-PCR and publicly available microarray data indicate that the tomatoSlbZIP genes have distinct and diverse expression patterns in different tissues and developmental stages and many of the tomatobZIP genes might be involved in responses to various abiotic and biotic stresses as well as in response to light. Conclusions This genome-wide systematic characterization identified a total of 69 members in the SlbZIP family and the analyses of the protein features and gene expression patterns provide useful clues for further functional characterization of the bZIP transcription factors in tomato.